TEACHERS' EVALUATION ON THE 2013 CURRICULUM ENGLISHTEXTBOOK FOR 9TH GRADE STUDENTS IN INDONESIA - Gagan Ginanjar, - (2016)
The primary focus of this research is to investigate the strengths and weaknesses of English textbook for ninth grade students based on teachers' evaluation and to find out teachers' criteria regarding good English textbook. This research is descriptive qualitative study. The data were obtanied by using the triangulation method; textbook evaluation, interview, and document analysis. The first data gained by conducting evaluation on English textbook entitled "Think Globally Act Locally" based on the evaluation instrument developed by Mukundan (2012). Since the textbook evaluated on this research is the 2013 English textbook, evaluation instrument for the 2013 curriculum textbook provided by BSNP also used as a combination. The second data gathered by implementing interview to discover teachers' opinion on criteria of good English textbook. The third data obtained by identifying theories from several well-known textbook experts; Grant (1987), Sheldon (1988), Cunningsworth (1995), Ur (1996), Harmer (2001,2007), Richards (2001), McGrath (2002), and Mukundan (2012) to confirm and enhance the accuracy of the research. The findings showed that the strengths of the textbook are dominant compared to the weaknesses identified. In terms of good criteria English textbook, teachers point of views are approriate with the theories provided by the experts. However, the findings of the research also provide unexpected result discovered that weaknesses of the textbook could be covered by teachers' ability on implementing textbook in the process of teaching and learning. Keywords: Textbook Evaluation, Teachers' opinion, Criteria of Good English Textbook